Photocatalytic studies of CdS nanoparticles assembled on carbon microsphere surfaces with different interface structures : from amorphous to graphite-like carbon - Liu, Yu (2013)
A rapid microwave-assisted method was used for the accurate coating of CdS nanoparticles on the surface of colloidal carbon microspheres to form C/CdS hybrid microspheres, which demonstrated enhanced visible-light-photocatalytic activity for the degradation of rhodamine B (RhB). To investigate the optimal photocatalytic synergistic effect, the above as-prepared of C/CdS hybrid microspheres were treated in a tube furnace by annealing at different temperatures (from 300 to 800 °C) in a N2 flow, which resulted in CdS nanoparticles assembled on different carbon layers (from amorphous to graphite-like carbon). The changes in FT-IR and Raman spectra that were caused by different interfaces were studied. Further, the synergic effect between CdS nanoparticles and different carbon layers, which influence the photocatalytic activity, was then investigated systematically. The results show that the photocatalytic activity of these samples was gradually enhanced as the calcination temperature increased. But compared to the sample without calcination, the photocatalytic activity decreases first and then increases. The combination of CdS and graphite-like carbon may be an ideal system to cause a rapid photoinduced charge separation and decreased possibility of recombination of electron–hole pairs by taking advantage of graphite-like carbon's unique electron transport properties, which increase the number of holes participating in the photooxidation process and enhance the photocatalytic activity.